The relationship between unemployment and economic growth: is Okun's Law valid for the Jordan case? - Omar Al-kasasbeh (Yayasan Riset dan Pengembangan Intelektual, 2022)
The purpose of this paper is the validity of Okun’s Law for Jordan’s economy over the period 1990 to 2020. The relation between unemployment and economic growth was tested. It aims to analyze the impact of unemployment on economic growth and to propose recommendations for enhancing economic growth and reducing unemployment in Jordan since the Jordanian economic growth was slow before the Covid-19 outbreaks. The research employed ARDL Bound Cointegration method having validated it’s appropriateness withDickey-Fuller and Philips-Perron tests. The empirical results reveal the existence of Okun’s law in the Jordan economy, with a 1% decrease in Gross Domestic Product which is correlated with a 0.276% increase in the unemployment rate. Based on these empirical outcomes, several policy recommendations are formulated to increase the attraction of foreign direct investment (FDI)which is needed to minimize the country's high unemployment rate. Jordan's policymakers are urged to embrace both labor and growth-inducing measures.